Redox Control of the Immune Response in the Hepatic Progenitor Cell Niche - Bellanti, Francesco; Pannone, Giuseppe; Tartaglia, Nicola; Serviddio, Gaetano (Frontiers in Cell and Developmental Biology, 2020)
The liver commonly self-regenerates by a proliferation of mature cell types. Nevertheless, in case of severe or protracted damage, the organ renewal is mediated by the hepatic progenitor cells (HPCs), adult progenitors capable of differentiating toward the biliary and the hepatocyte lineages. This regeneration process is determined by the formation of a stereotypical niche surrounding the emerging progenitors. The organization of the HPC niche microenvironment is crucial to drive biliary or hepatocyte regeneration. Furthermore, this is the site of a complex immunological activity mediated by several immune and non-immune cells. Indeed, several cytokines produced by monocytes, macrophages and T-lymphocytes may promote the activation of HPCs in the niche. On the other side, HPCs may produce pro-inflammatory cytokines induced by liver inflammation. The inflamed liver is characterized by high generation of reactive oxygen and nitrogen species, which in turn lead to the oxidation of macromolecules and the alteration of signaling pathways. Reactive species and redox signaling are involved in both the immunological and the adult stem cell regeneration processes. It is then conceivable that redox balance may finely regulate the immune response in the HPC niche, modulating the regeneration process and the immune activity of HPCs. In this perspective article, we summarize the current knowledge on the role of reactive species in the regulation of hepatic immunity, suggesting future research directions for the study of redox signaling on the immunomodulatory properties of HPCs.